(untitled) - Ware, Edith E. (London, 1932)
This book introduce about the business contractual relationships in China: Their bearing upon abolition of extraterritoriality. In summary and in transition. International cooperation versus militarism. Business and politics in the far east.
Keywords: Exterritoriality,Ngoại giao